Latkes and Applesauce, A Hanukkah Story - Manushkin, Fran; Easler, Kris (Watertown, MA : Charlesbridge, 2022)
When a blizzard leaves a family housebound one Hanukkah, they share what little food they have with some starving animals who later return the favor.
Keywords: Hanukkah stories; Jewish families -- Juvenile fiction; Latkes -- Juvenile fiction; Compassion -- Juvenile fiction; Conduct of life -- Juvenile fiction; Hanukkah -- Fiction; Family life -- Fiction; Latkes -- Fiction; Compassion -- Fiction; Conduct of life -- Fiction; Picture books